LevRad software as a tool to learn how to proceed with an evaluation of barriers - Ferreira, C. C.; Souza, S. O. (Cellular and Molecular Biology, 2011)
We developed the software LevRad with the objective of teaching how to proceed in an analysis of barriers shielding against x-rays to minimize the contact of the professional or the student with x-rays and also to prevent wearing out of the x-ray equipment. Some tests of the software were made, and preliminary results indicate that LevRad is efficient as a complementary tool for the development of professionals related to diagnostic radiology. In the case of education, an advantage is gained when the beginner uses the software before his or her first contact with x-ray equipment in locu. The software introduces a basic knowledge about evaluation of barriers, prevents wearing out of the x-ray tube, reinforces teaching of evaluation of barriers, and reduces the collective effective dose by avoiding unnecessary exposures when possible.